Tingkat Kecerdasan Sosial Mahasiswa Fakultas Keguruan dan Ilmu Pendidikan Universitas Kanjuruhan Malang - Laily Tiarani Soejanto; F.I. Soekarman (JKI (Jurnal Konseling Indonesia), 2015)
Specifically this study attempts to 1) provide information accurate data about levels of students social intelligence 2) To present an accurate data about the level of students social intelligence based on ethnicity. This research use descriptive- quantitative methodology. This research use purposive sampling of 120 students Faculty of Education. Research instrument used social intelligence scale consisting of 70 items. Data were processed using descriptive statistics and ANOVA test. Based on these results we can conclude that 1) 61.7% Students are at a high level of social intelligence, 38.3% Students are at moderate levels of social intelligence, 0% Students are at a low level of social intelligence; 2) There are significant differences between the scores of social intelligence in all regions.